Is Australia Ready for Autonomous Vehicles? Examining the Factors Influencing AV Adoption through Expert Interviews - Lim, Wesley; Lee, Sean; Sung, Billy; Cronin, Sophie (Elsevier, 2023)
As Autonomous Vehicles (AVs) on public roads today becomes an increasingly realistic possibility, there is growing need to better understand the factors that will facilitate their successful introduction. This study focuses specifically on Australia and investigates various micro and macro environmental factors that may either hinder or support their adoption in the country. The study comprised 18 in-depth interviews with experts from both the public and private sectors who possess direct experience working with AVs. These experts provided valuable insights into several areas, including the legislation and regulations governing AV use, the technical and infrastructure requirements necessary for safe operation on public roads, and the importance of public sentiment in driving AV adoption and introduction. Based on the study’s findings, an integrated framework has been developed to identify and classify the key factors related to AV adoption, as well as their interrelatedness with each other. This framework seeks to guide the development of national strategies to accommodate the necessary political, legal, and social adjustments required for the successful implementation of AVs.